Linguística de la escritura Debates entre lengua y literatura - FABB, Nigel comp. (VISOR, 1989)
CONTENIDO : COLABORAN MacCABE, COLIN; WILLIANS,R.; PRATT, M.L.; HALLIDAY,M.A.K.; CULLER, J.; JAMERSON, F.; DERRIDA, J.; FISH, S.; HALLE, M.